Food Supply Chain Network and Market Analysis of Shallot in Indonesia (Case Study: Brebes District) - Nurunisa, Venty Fitriany; Hotman, Jan; Rifin, Amzul; Wicaksana, Bayu Eka; Sigit, Argadatta (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Brebes District, recognized as the largest shallot producer in Indonesia, continues to face challenges in ensuring the welfare of its shallot farmers. This situation emerged from a complex network of stakeholders involved in shallot agribusiness in the Brebes District, characterized by a significant presence of intermediaries. Purpose: This research aims to i) analyze the shallot supply chain in the Brebes District by applying the Food Supply Chain Network (FSCN) approach and ii) examine its performance through marketing margin and farmer share. Design/methodology/approach: Data was gathered through interviews with 83 shallot farmers and 12 marketing actors in the Brebes District. Additionally, a Focus Group Discussion (FGD) was conducted to gather strategic insights from all stakeholders involved in the shallot agribusiness in the Brebes District. The research used a qualitative approach to answer the FSCN analysis and a quantitative approach to measure the supply chain performance.Findings/Result: This study identified that the supply chain had clear objectives and structured relationships between actors. However, it was not optimized because the business process was not integrated into the long term. The supply chain involved multiple marketing channels, where each level of intermediary had involvement and impact on farmer share and margins. More direct marketing channels, such as Marketing Channel I, where farmers sell directly to village traders, offer the highest farmer share (89%) due to the absence of intermediaries like wholesalers. In contrast, channels involving more intermediaries, such as wholesalers in Channels III and V, result in higher total margins but a lower farmer share (81%). Conclusion: The FSCN analysis of shallots in the Brebes District reveals a complex marketing system with various channels. Direct marketing channels give farmers the highest share by removing intermediaries, while those with more intermediaries offer higher total margins but lower farmer shares. Reducing intermediaries is recommended to boost farmer incomes. Additionally, inefficiencies like poor coordination and limited access to market information hinder overall performance.Originality/value (State of the art): This study introduces a novel application of the FSCN approach to comprehensively analyze the shallot supply chain in Brebes District, Indonesia. The FSCN offers insights into the complex relationships between farmers, traders, and other actors, their challenges, and the potential for improving the system's efficiency. Keywords: shallot, information sharing, marketing actors, marketing channels, supply chain efficiency